Differential neuromodulatory role of endocannabinoids in the rodent trigeminal sensory ganglion and cerebral cortex relevant to pain processing. (15th March 2018) - Eroli, Francesca; Loonen, Inge C.M.; van den Maagdenberg, Arn M.J.M.; Tolner, Else A.; Nistri, Andrea
Abstract: Endocannabinoids are suggested to control pain, even though their clinical use is not fully validated and the underlying mechanisms are incompletely understood. To clarify the targets of endocannabinoid actions, we studied how activation of the endocannabinoid CB1 receptor (CB1R) affects neuronal responses in two in vitro preparations of rodents, namely the trigeminal sensory ganglion (TG) in culture and a coronal slice of the cerebral cortex. On TG small-medium size neurons, we tested whether submicromolar concentrations of the endogenous CB1R agonist anandamide (AEA) modulated inhibitory GABAA receptors and excitatory ATP-gated P2X3 receptors. AEA reversibly depressed GABA-mediated membrane currents without altering P2X3 receptor responses. The AEA antagonism was non-competitive, prevented by the CB1R antagonist AM-251, mimicked by the other cannabinoids 2-arachidonylglycerol and WIN 55, 212-2, and insensitive to TRPV1 blocker capsazepine. AEA inhibited the potentiation of GABAergic responses by the cAMP activator forskolin, in line with the canonical inhibition of cAMP synthesis by CB1Rs. In the cerebral cortex, AEA or WIN 55, 212-2 did not affect electrically-evoked local field potentials or characteristics of cortical spreading depolarization (CSD) elicited by high potassium application. The GABAA receptor blocker gabazine, however, strongly enhanced field potentials without affecting CSD properties, suggesting that CSD was not dominantly controlled by GABAergic mechanisms. Our data propose that, despite the widespread expression of CB1Rs peripherally and centrally, the functional effects of AEA are region-specific and depend on CB1R coupling to downstream effectors. Future studies concerned with the mechanisms of AEA analgesia should perhaps be directed to discrete subcortical nuclei processing trigeminal inputs. Highlights: Anandamide (and WIN55, 212-2) block GABA receptors of trigeminal sensory neurons. Such inhibition is mediated by CB1 receptors and block of cAMP synthesis. Cortical spreading depolarization is unaffected by anandamide or gabazine. Cortical network transmission is enhanced by gabazine but insensitive to anandamide. Endocannabinoid modulation of GABAergic mechanisms is brain region-specific.